Developing a mechanism-based therapy for acute psychiatric inpatients with psychotic symptoms: an Intervention Mapping approach - Gussmann, Eva; Lucae, Susanne; Falkai, Peter; Padberg, Frank; Egli, Samy; Kopf-Beck, Johannes (Frontiers in Psychiatry, 2023)
Treatment guidelines for psychosis recommend offering psychotherapy already in the acute illness phase. However, there is a lack of available interventions adapted to the specific needs and key change mechanisms of inpatients experiencing severe symptoms and crisis. In this article we outline the scientific development process of a needs-oriented and mechanism-based group intervention for acute psychiatric inpatients with psychosis (MEBASp). To guide our intervention design, we used Intervention Mapping (IM), a six-step framework for developing evidence-based health interventions that consisted of an extensive literature review, an in-depth problem definition and needs analysis, the modelling of change mechanisms and outcomes and the production of an intervention prototype. Our low-threshold modularized group intervention consists of nine stand-alone sessions (two per week) within three modules and targets different aspects of metacognitive and social change mecha-nisms. Module I and II aim to reduce acute symptoms by fostering cognitive insight, Module III fo-cuses on reducing distress via cognitive defusion. Therapy contents are adapted from existing meta-cognitive treatments such as the Metacognitive Training and presented in a destigmatizing, simply understandable and experience-oriented way. MEBASp is currently evaluated in a single-arm feasibil-ity trial. Using a systematic and rigorous development methodology and providing a detailed descrip-tion of the development steps demonstrated to be invaluable in improving the intervention’s scientific foundation, validity, and replicability for similar research.